THE APPLICATION OF GAMIFICATION TO IMPROVE SPEAKING CAPABILITIES IN LANGUAGE ACQUISITION (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
The use of game design principles outside of games, or gamification, has become a potent teaching and learning aid, especially for language acquisition. The use of gamification to improve speaking abilities is examined in this article. Gamification has the potential to revolutionize traditional speaking exercises by including components like leaderboards, badges, points, and interactive challenges, which may provide an exciting and motivating learning experience. This essay examines the theoretical underpinnings of gamification, its advantages for improving speaking abilities, and useful application techniques. We show how gamification may greatly enhance learners' speaking skills and general language competency through in-depth study and case studies.